AB0576 Ophtalmologic Findings in Patients with Takayasu's Arteritis. (15th July 2016) - Kelesoglu, A.B.; Baytaroglu, A.; Sari, A.; Erden, A.; Kilic, L.; Tatar, O.; Karadag, O.; Kalyoncu, U.; Ertenli, I.; Apras Bilgen, S.
Abstract : Background: Takayasu's Arteritis (TA) is a large vessel vasculitis of young females. Ophtalmologic findings as wreath-like arteriovenous anastomosis around the optic disc are the firstly described clues for TA. Opthalmologic pathologies could have negative impact on quality of life but, there are limited data about ocular manifestations of TA. Objectives: To investigate the ophthalmologic manifestations of TA. Methods: In this cross-sectional study 33 TA (F/M: 29/4) patients were evaluated. Demographic and clinical findings were recorded from hospital files. Addition to routine examination, anterior segment and fundus of eyes were assessed. Results: The median age at the time of ocular examination was 38 (min-max:19–62) years and mean disease duration was 5.7±5.5 years. Two (6.1%) patients had diabetes mellitus, 13 (39.4%) patients had hypertension. Only one patient had cranial involvement of TA. Most of the patients had been taking immunosuppressive agents addition to corticosteroids [Methotrexate (n=11, (33.3%)), cyclophosphamide (n=9, (27.3%)), azathiopurine (n=5, (15.2%)), one patient for each mycophenolate mophetil, infliximab, tocilizumab] Of patients 15 (45.4%) had pathologic findings in opthalmologic examinations. Twelve patients (36.4%) had anterior segment pathology, 10 (30.3%) patients had posterior segment pathology. Of these patients 7 (21.2%) had both anterior and posterior segment pathology. Distribution of anterior segment pathologies were; 9 (27.2%) patients had cataract, 2 (6.1%) patients had dry eyes and one patient had congenital disgenesis. In fundoscopic examination of posterior segment, hypertensive retinopathy was the most frequent pathologic finding as 12.1% (n=4) Three of these patients have had diagnosis of essential hypertension and were treated with anti-hypertensive medication One patient had ocular ischemic syndrome which is typical for TA (Table 1 ). Conclusions: In the early results of our study, disease or treatment related ocular pathologic findings were frequent in TA. Periodic consultation and ophthalmologic examination of TA patients might be rational approach in follow up of these patients. Disclosure of Interest: None declared